A Study of Supply Chain Management for Sustainable Solid Waste Plan in Perhentian Island, Terengganu - Jumadil Saputra; Siti Aisyah Saat; Rahaya Md Jamin; Rosyidah Muhamad; Rozita Muhamad Nawi (International Journal of Supply Chain Management, 2019)
Solid waste management is a serious environmental issue for marine park islands in Malaysia. With the rapid growth of non-systemic solid waste management problems generated by the tourism industry. The amount of waste generated by massive visitors is a difficult problem in small islands as it is usually produced within a short period of time and adds to the existing waste management problems. This study is aimed at identifying the sustainability level of solid waste management in Perhentian Island, Terengganu. Therefore, this study proposed waste management plans for Perhentian Island in order to achieve sustainability of solid waste management in Small Island. Inefficient solid waste management will not only cause a deterioration in tourist arrivals to the island but it also has a negative impact on the quality of the Perhentian island environment. The study using qualitative approaches, in-depth interviews with chalet operators and Besut district Council officials in relation to the management of solid waste management on the island. The study found that integrated recycling program approaches and composting methods were seen to be more efficient for use to ensure sustainable solid waste management in Perhentian Island.